2000
DOI: 10.1017/s1463981500040723
|View full text |Cite
|
Sign up to set email alerts
|

The effect of whole linseed or xylose treated whole linseed on dairy cow performance and level of the fatty acids C18:3, C20:5and C22:6in milk fat

Abstract: The Committee on Medical Aspects of Food Policy report Nutritional Aspects of Cardiovascular Disease recommended increased dietary intakes of the long chain polyunsaturated fatty acids eicosapentaenoic acid and docosahexaenoic acid to help protect against cardiovascular disease. There is some evidence that a-linolenic acid can be elongated and desaturated by mammalian enzyme systems to produce small amounts of eicosapentaenoic and docosahexaenoic acids. Whole linseeds are rich in a–linolenic acid, and it has b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…[1]), under this hypothesis, could be partly explained by the decrease in C4 to C16 yield. Indeed, when lipid supplementation does not induce a decrease in de novo synthesis (e.g., protected lipid sources), there are high increases in milk C18 yield (Bartsch et al, 1976;Goering et al, 1977;Mansbridge et al, 1999;Goodridge et al, 2001).…”
Section: Determinants Of C18 Yieldmentioning
confidence: 99%
“…[1]), under this hypothesis, could be partly explained by the decrease in C4 to C16 yield. Indeed, when lipid supplementation does not induce a decrease in de novo synthesis (e.g., protected lipid sources), there are high increases in milk C18 yield (Bartsch et al, 1976;Goering et al, 1977;Mansbridge et al, 1999;Goodridge et al, 2001).…”
Section: Determinants Of C18 Yieldmentioning
confidence: 99%
“…Results in this study also showed that the concentration of C18:3n3 in creams from the linseed group increased significantly (P < 0.01), and this may be attributed to the FA composition of linseed because a rich source of C18:3n3. Previous studies about the effect of fat-supplemented rations on FA profile found that linseeds increased the proportion of C18:3n3 up to 1.5% of total FA (Kennelly 1996;Mansbridge et al 1999) and the C18:3n3 content was maximised SFA, sum of all saturated fatty acids; SC-SFA, total short-chain saturated fatty acids (C4-C10); MC-SFA, total medium-chain saturated fatty acids (C12-C16); LC-SFA, total long-chain saturated fatty acids (>C17); UFA, sum of all unsaturated fatty acid; MUFA, sum of all monounsaturated fatty acids; PUFA, sum of all polyunsaturated fatty acids; TFA, sum of total trans-fatty acids; CLA, sum of cis-9, trans-11C18:2 and other CLA isomers; n3-PUFA, sum of all n3 polyunsaturated fatty acids; n6-PUFA, sum of all n6 polyunsaturated fatty acids. Index of D9-desaturase was calculated according to Malau-Aduli et al (1997).…”
Section: Resultsmentioning
confidence: 98%
“…Previous studies about the effect of fat‐supplemented rations on FA profile found that linseeds increased the proportion of C18:3 n 3 up to 1.5% of total FA (Kennelly ; Mansbridge et al . ) and the C18:3 n 3 content was maximised when cows were fed with full fat linseeds (Secchiari et al . ).…”
Section: Resultsmentioning
confidence: 99%